Elit kadın voleybolcularda iki farklı dirençle blok antrenman yönteminin alt ekstremite güç, blok adımlama hız ve mesafesine etkisi - Yarkın, Gençer (My University, 2025)
Amaç: Bu çalışmanın amacı voleybolda çapraz adım blok tekniğinin hızının artırılması için iki farklı direnci içeren yüklü kızak ve direnç lastiği ile blok adımlaması antrenmanlarının etkisinin araştırılması ve blok adımlama evrelerinin ivme, hız ve kat edilen mesafe parametrelerinin incelenmesidir. Gereç ve Yöntem: Çalışma 16-32 yaş aralığında (n =29) kadın voleybolcudan oluşmuştur. Yüklü kızak grubu (YKG), direnç lastiği grubu (DLG) ve kontrol grubu (KG) olmak üzere 3 grup oluşturulmuştur. Ön test son test ölçümleri yapılmıştır. Çapraz adım blok adımlaması ölçümlerinde ivme ölçer sensör kullanılmıştır. Dört hafta boyunca, haftada iki defa antrenman uygulaması yapılmıştır. Verilerin İstatistiksel analizinde antrenman etkinliği için Tekrarlı Ölçümler ANOVA ve ANCOVA, blok adımlamasının evrelerinin ivme, hız ve kat edilen parametrelerdeki farkları ise Tekrarlı Ölçümler ANOVA ile sınanmıştır. Anlamlılık değeri p<0,05 olarak belirlenmiştir. Bulgular: Gruplar arası ivmelenme değerinde anlamlı bir fark bulunamamıştır (p>0,05). DLG ve YKG toplam hızı sağ ve sol yönde KG'ye göre istatistiksel olarak fark gözlenmiştir (p<0,05). Kat edilen mesafe göz önüne alındığında DLG istatistiksel olarak sol yönde KG'ye göre gelişim göstermiştir (p<0,04). Ortalama ivme parametresinin evrelere göre sıralaması Evre 3>Evre 2>Evre 1 şeklindedir. Ortalama hız parametresine bakıldığında ise Evre 2 en hızlı, Evre 1 en yavaştır. En fazla mesafe Evre 2'de en az mesafe ise Evre 3'de kat edilmiştir. Sonuç: DLG ve YKG toplam blok adımlaması ve evrelerde hız, mesafe performansları artmıştır. Hız performansı için her iki dirençli egzersiz, mesafe artışı için direnç lastiği avantajlı görünmektedir. En yüksek ortalama ivme değeri Evre 3'e, en hızlı Evre 2, yüksek pozitif ivme oranına sahip evrenin Evre 1 ve en yüksek negatif ivme orana sahip evrenin de Evre 3 olduğu ortaya koyulmuştur.

Objective: The aim of this study was to investigate the effect of cross-over step block training with loaded sled and resistance band exercises, incorporating two different resistance levels, on enhancing the speed of the cross-over step block technique in volleyball. Additionally, the study aimed to examine the acceleration, velocity, and distance traveled during the phases of the block stepping. Materials and Methods: This study included female volleyball players aged 16 to 32 years (n = 29), who were divided into three groups: the loaded sled group (LSG), the resistance band group (RBG), and the control group (CG). Pre-test and post-test measurements were conducted. An accelerometer sensor was used to measure cross-over step block stride parameters. The training program was implemented twice per week over a four-week period. For statistical analysis, Repeated Measures ANOVA and ANCOVA were used to evaluate training effectiveness, while the differences in block stepping phases in terms of acceleration, velocity, and distance traveled were assessed using Repeated Measures ANOVA. The significance level was set at (p<0.05). Results: No significant difference in acceleration values was found between the groups (p>0.05). However, a statistically significant difference was observed in the total speed of the LSG and RBG during cross-over step blocking in both the right and left directions (p<0.05). Regarding the distance traveled during blocking, the RBG showed a statistically significant improvement in the left direction compared to the CG (p<0.04). The mean acceleration parameter throughout the three phases of cross-over step blocking followed the order: Phase 3> Phase 2>Phase 1. Phase 2 was the fastest, while Phase 1 was the slowest. The peak distance was traveled in Phase 2, whereas the minimum distance was traveled in Phase 3. Conclusion: The performance of both the RTG and LSD improved in total block stepping and throughout the phases of blocking. Both resistance training methods appeared to be advantageous for velocity, while RTG demonstrated greater benefits in increasing distance during cross-over step blocking.
The effect of two different resistive block training methods on lower extremity power, block stepping speed and distance in elite female volleyball players
Keywords: acceleration; block; blok; Egzersiz; Exercise; güç Volleyball; hız; ivmelenme; Kadınlar; power; Turkey; Türkiye; velocity; Voleybol; Voleybolcular; Volleyball players; Women